Whole genome bisulfite sequencing reveals unique adaptations to high-altitude environments in Tibetan chickens - Zhang, Zengrong (PLoS One, 2018)
BACKGROUND: Tibetan chickens living at high altitudes show specific adaptations to high-altitude conditions, but the epigenetic modifications associated with these adaptations have not been characterized. RESULTS: We investigated the genome-wide DNA methylation patterns in Tibetan chicken blood by using whole genome bisulfite sequencing. Generally, Tibetan chickens exhibited analogous methylation patterns to that of lowland chickens. A total of 3.92% of genomic cytosines were methylcytosines and 51.22% of cytosines in CG contexts were methylated, which was less than those in lowland chicken (55.69%). Moreover, the base adjacent to the methylcytosines of mCHGs in Tibetan chickens had a preference for T, which was different from that in lowland chickens. In Tibetan chickens, the methylation levels in the promoter were relatively low, while the gene body was also maintained in a hypomethylated state. DNA methylation levels in regions upstream of the transcription start site of genes were negatively correlated with the level of gene expression, and DNA methylation of gene body regions was also negatively related to gene expression. CONCLUSIONS: We generated the genome-wide DNA methylation patterns in Tibetan chickens and our results will be helpful for future epigenetic studies related to adaptations to high-altitude conditions.